193k views
0 votes
Another question for math. ill give mad points, the question is in attachment

Another question for math. ill give mad points, the question is in attachment-example-1
User Ejolly
by
6.4k points

1 Answer

5 votes
For this case we have the following points:
y = (- 2, 5)
z = (1, 3)
Therefore, the vector yz is given by:
yz = z - y = (1, 3) - (-2, 5)
yz = ((1 - (- 2)), (3-5))
yz = ((1 + 2), -2)
yz = (3, -2)
Then, the magnitude is given by:
lyzl = root ((3) ^ 2 + (-2) ^ 2)
lyzl = root (9 + 4)
lyzl = root (13)
Answer:
yz = (3, -2)
lyzl = root (13)
option A
User Johnstaveley
by
5.8k points